1983
DOI: 10.1590/1809-439219831356911
|View full text |Cite
|
Sign up to set email alerts
|

Relação dos tipos de invertebrados depositados na Coleção de Entomologia Sistemática do INPA - Manaus, até dezembro de 1982

Abstract: Resumo (4):689-698). Naquela lista alguns erros foram cometidos; alguns tipos dados como perdidos foram encontrados e alguns tipos depositados em outras coleções do próprio Instituto foram reunidos para constituir uma única coleção, que se encontra atualmente no pré-dio da Ecologia -V.8. Apesar do esforço de tentarmos reunir todos os espécimens tipos numa única coleção, tal intento não foi conseguido, razão pela qual, neste trabalho, listamos apenas os tipos que realmente se encontram no acervo da Coleção de E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

1984
1984
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Specimens of two Rotifera species were listed in former catalogues (RATCLIFFE & PENNY 1978b, RAFAEL et al 1983) as being holotypes. A closer examination of the data associated to these material revealed that they cannot be considered as such.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Specimens of two Rotifera species were listed in former catalogues (RATCLIFFE & PENNY 1978b, RAFAEL et al 1983) as being holotypes. A closer examination of the data associated to these material revealed that they cannot be considered as such.…”
Section: Resultsmentioning
confidence: 99%
“…ALTHERR (1972,1977) described several new species of Nematoda from a collection made by W. Sattler in 1961 in interstitial waters near Benfica (01º18'S, 48º18'W) in the vicinity of Belém, state of Pará, Brazil, and stated that the types were deposited at INPA. However, these types have never been found in the Collection of Invertebrates at INPA and they were not listed in its two former catalogues of type specimens (RATCLIFFE & PENNY 1978b, RAFAEL et al 1983). Edmond Altherr died in November of 1976, and he probably did not have the opportunity to send these types back to INPA.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Because of unclear type designations in the taxonomical description, type specimens of seven Amazonian Diaptomidae species and one Bosminidae species were listed as syntypes in the Systematic Entomology Collections of the Instituto Nacional de Pesqui sas da Amazônia -1NPA) in Manaus, Brazil (cf. Ratcliffe & Penny, 1978;Rafael et al, 1983).…”
mentioning
confidence: 99%